Monitoring Environmental and Structural Parameters in Historical Masonry Buildings Using IoT LoRaWAN-Based Wireless Sensors - Noëlla Dolińska; Gabriela Wojciechowska; Łukasz Bednarz (Buildings)
This study investigates the impact of environmental conditions on the structural integrity and energy dynamics of historical masonry buildings using an IoT (Internet of Things) LoRaWAN-based (Long Range Wide Area Network) wireless sensor system. Over a six-month period, sensors were used to monitor wall temperature, wall humidity, air temperature, air humidity, crack width, and crack displacement. The data revealed significant correlations between environmental parameters and structural changes. Higher temperatures were associated with increased crack width, while elevated humidity levels correlated with greater crack displacement, showing the potential weakening of the masonry structure. Seasonal variations highlighted the cyclical nature of these changes, emphasizing the need for seasonal maintenance. Additionally, the findings suggest that managing temperature and humidity levels can optimize the building’s energy efficiency by reducing the need for additional heating or cooling. The use of LoRaWAN sensors provided real-time, remote monitoring capabilities, offering a cost-effective and scalable solution for preserving historical buildings. This study underscores the importance of continuous environmental and structural monitoring for the preservation of heritage sites. It also highlights the potential for integrating proactive maintenance strategies and energy optimization, ensuring long-term sustainability. By leveraging this IoT-based approach, this research contributes to the broader field of heritage conservation, offering a universal framework that can be applied to historical buildings worldwide, enhancing both their structural integrity and energy performance.